Avaliação hematológica de sangue e medula óssea e bioquímica sérica de cães infectados naturalmente por hemoparasitas - Mariana de Padua Costa (2014)
Hemoparasitoses presents high prevalence and importance in small animal clinical, resulting in a variety of haematological disorders. This study has the objetive to evaluate the hematological changes in blood, bone marrow and serum biochemistry in dogs naturally infected by Ehrlichia sp., Ehrlichia canis, Anaplasma platys, Babesia canis canis and Leishmania sp., diagnosed by PCR and to compare to non infected dogs, despite clinical suspect. Hemoparasites co-infections are relatively common in dogs, occurring in 42.9% (27/63) of the studied animals. Clinical pathological alterations were exacerbated in co-infections, and included anemia (85.7%), thrombocytopenia (57.1%) and variable response of leukocytes. Bone marrow evaluation demonstrated variations in infected animals according to the stage of infection and infectious profile.Changes in biochemical analytes were frequent in animals with hemoparasitoses, highlighting the values of albumin, alkaline phosphatase and alanine aminotransferase in animals infected with Ehrlichia canis. Infection by Leishmania sp. was associated with decreased levels of albumin and increased levels of globulins. It was observed higher incidence of anemia (77,8% versus 33,3%), trombocytopenia (55,6% versus 28,6% ), leukocytosis (18,5% versus 14,3%), leukopenia (14,8% versus 4,8%), hypergammaglobulinemia (40,7% versus 14,3%) and bone marrow hypocellularity (53,8% versus 0% ) in animals infected by hemoparasites. Haematological blood tests and bone marrow and serum biochemistry can help to diagnose hemoparasitoses in dogs, although there is no golden test.